Nanocrystallization: An Effective Approach to Enhance the Performance of Organic Molecules. Issue 3 (12th January 2017) - Fateminia, S. M. Ali; Wang, Ziqiao; Liu, Bin
Abstract : Organic nanocrystals have attracted great research interest in recent years due to their superior physical and chemical properties as compared to their amorphous counterparts. Higher photoluminescence intensity, steadier dissolution, and greater structural stability are a few examples of these properties, making nanocrystals an excellent choice for a wide range of applications, like electronics, bioimaging, and pharmaceuticals. Here, the principles of the most important nanocrystallization methods for organic compounds are elaborated. The discussion comprises the most important top‐down and bottom‐up approaches reported so far, explaining their advantages and limitations. To address the limitations of these methods, a new bottom‐up concept of stress‐induced seed‐assisted nanocrystallization is proved to be universally applicable to different organic molecules. To close, the future perspectives in the field are discussed. Abstract : Organic nanocrystals possess superior physical and chemical properties as compared to their amorphous counterparts. Their special characteristics make them an ideal choice for a wide range of applications from microelectronics to biology. A thorough and comprehensive discussion on the most important fabrication methods of organic nanocrystals is presented.